منهج مقترح لتعليم اللغة العربية من خلال النظائر المخادعة بين اللغة اللامبونجية واللغة العربية في معجم اللغة اللامبونجية للامبونجيين - M. Syarif Hidayatullah; Zulkhaidir (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2020)
This study aimed at designing a suggested curriculum for teaching Arabic through Arabic homonim in Lampung-Indonesia Dictionary for Lampung People. In order to ending this study, the researcher followed the descriptive analytical method, through which the researcher collected similar Lampung words in Arabic, and identified and analyzed them. Then the researcher put it in a unit of study to be a suggested educational curriculum for teaching the Lampung people the Arabic language. This study found that the number of similar Lampung words in the Arabic language or Arabic homonim in Lampung-Indonesia Dictionary is 153 words. And I proved that those words in terms of their pronunciation are divided into two parts: a section in which the pronunciation of the Arabic and Lampung words is matched, and a section in which the pronunciation is a simple deviation. And that the proposed curriculum for teaching it is the curriculum focused on the four language skills: speech skill, listening skill, reading skill and writing skill.